Efficiency of the occlusion therapy with and without levodopa-carbidopa in amblyopic children-A tertiary care centre experience - Sofi, Ishfaq Ahmad; Gupta, Satish K; Bharti, Anuradha; Tantry, Tariq G (International Journal of Health Sciences, 2016)
Objectives: To assess the role, efficacy and tolerability of levodopa-carbidopa in the management of small and older children with different types of amblyopia. Methodology: Prospective randomised placebo controlled clinical study, in which 50 amblyopic patients between 5 and 20 years of age with visual acuity (V/A) < 20/40 were included, was carried on. After having attained the best possible refractive correction, patients were randomly divided into 2 groups. They were prescribed levodopa-carbidopa (10:1) (4-6mg/kg/day in 2-3 divided doses) or placebo, plus full-time occlusion of the sound eye, for a period of three months. Assessment of improvement in V/A, compliance and tolerance was done at follow up visits. Data was analyzed using computer software Ms-Excel and Epi-Info Version 6.0. The statistical significance was assessed by Chi-Square/Fisher’s Exact Test. Results: Visual acuity for the amblyopic eye improved significantly in both groups but there was significant improvement in group1 than group 2 (P = 0.0001). In a subgroup of patients older than 12 years, levodopa group showed statistically significant improvement in baseline V/A (P = 0.0001). In patients with severe amblyopia, each group showed significant improvement in baseline V/A (p < 0.05), but was significantly more in group1 (P = 0.0001). Compliance rates were similar among the groups and levodopa-carbidopa at a dose range of 4-6 mg/kg/day was well tolerated. Conclusion: Levodopa-carbidopa can be used as an adjunct to conventional occlusion therapy in amblyopia particularly in older children and severe cases of amblyopia, and it is well tolerated. Keywords: Amblyopia, Levodopa-carbidopa, Occlusion therapy.